Evaluasi Pengembangan Indikator Kinerja Studi pada Badan Pusat Statistik (BPS) - Husaini Husaini (ABIS: Accounting and Business Information Systems Journal, 2015)
This study aims to evaluate the performance indicator development process in BPS; analyze whether BPS’s performance indicators have described its performance; and identify the factors that play a role in the development of BPS’s performance indicators. This study uses a qualitative approach with a case study method, in which the views or opinions of participants are the key to address the existing problems. The results show that the performance indicator development at BPS hasn’t been done well because there are still discrepancies of information, both among the BPS planning documents and with the target performance. BPS’s performance indicators are considered as not describing the designated performance because it is still oriented to the effort, and not the result. The factors that play a role in BPS’s performance indicator development include: management support, technical competence, regulatory demands, statistics development in other countries; whereas the impeding factors are availability of performance data, lack of internal commitment, conflict of interest, and stakeholder’s divergent understanding of official statistics.